The name is the game : onomatology and the genealogist - Bockstruck, Lloyd DeWitt (Published for Clearfield Company by Genealogical Publishing Company, 2013)
"Names, like people, have lives of their own, which is why Lloyd Bockstruck's new book about the serendipity and life's choices that can alter our family names is must-reading for every researcher. Mr. Bockstruck, one of America's foremost genealogists and the former genealogy librarian at the Dallas Public Library, has distilled the wisdom of a lifetime about the vagaries of names into this work. Eminently readable, The Name IS the Game is a collection of illustrations and cautionary tales that can help family historians surmount the obstacles or avert the pitfalls associated with naming practices throughout the centuries. The book is divided into five chapters, and it engages the reader at the get-go. For instance, in the introductory first chapter Bockstruck relates a number of first-hand accounts that fostered his early fascination with names, such as his initial failure to find the tombstone of German great-aunt Barbara Baker (born Barbara Becker). The introduction's high point is the incredible story of the peregrinating Scots colonist Ian Ferguson, whose name was recorded as Johann Feuerstein when he was among the Pennsylvania Palatine immigrants, and was later recorded as John Flint when he moved to Philadelphia. Two generations later, one of his grandsons, Peter Flint, moved to Louisiana, where he was recorded as Pierre a Fusil, only to end up as Peter Gunn when he settled in Texas after the Civil War"--Publisher description